PENINGKATAN KUANTITAS DAN KUALITAS USAHA KOPI BUBUK DI DESA PERMU KECAMATAN KEPAHIANG KABUPATEN KEPAHIANG - Alnopri -; Prasetyo Prasetyo; Yessi Rosalina (DHARMA RAFLESIA, 2018)
Community service activities have been carried out in the Permu Village, Kepahiang Subdistrict, Kepahiang District. The target group is the group of mothers who take shelter Permu village in the "Tik Kerto". The purpose of this activity is to increase the number and improve the quality of coffee of Permu Village. The activities carried out by the method of illumination and field practice, transfer of technology, and promotion of products. Results show that a group of mothers who take the activities of in the village Permu Tik Kerto group are very enthusiastic and improving the quantity and quality of coffee products of Permu Village. Technology transfer processing using the ground coffee roaster machine is responded well and the quality of the resulting coffee powder are in accordance with SNI 01-3542-2004, the national standard of coffee. The conclusion of this activity is the formation of industry groups Tik Kerto coffee, coffee quality after transfer of technology is better than before, Permu Village coffee product of group of mothers Tik Kerto is improved. Suggestions for next years, implementation of the PPM complement of the activities carry out infrastructure and facilities for the production of ground coffee of Permu Village. Keywords: Coffee, Quantity and Quality Improvement, Permu Village